Estimating the Impacts of Plant Internal Nitrogen Deficit at Key Top Dressing Stages on Corn Productivity and Intercepted Photosynthetic Active Radiation - Zhao, Ben; Ata-Ul-Karim, Syed Tahir; Duan, Aiwang; Gao, Yang; Lou, He; Liu, Zugui; Qin, Anzhen; Ning, Dongfeng; Ma, Shoutian; Liu, Zhandong (Frontiers in Plant Science, 2022)
Accurate and timely appraisal of plant nitrogen (N) demand is imperative to regulate the canopy structure and corn production. The strength and time of plant N deficit can be quantified by critical N concentration. The study was aimed to analyze nitrogen nutrition index (NNI), nitrogen deficit content (NDC), plant nitrogen productivity (PNP), and fraction of intercepted photosynthetic active radiation (FIPAR) across different N treatments, and to develop NNI-NDC, NNI-PNP, NNI-FIPAR, NDC-PNP, and NDC-FIPAR relationships from V6 to V12 stages of corn to quantify the suitable PNP and FIPAR values under the optimal plant N condition. Four multi-N rate (0, 75, 90, 150, 180, 225, 270, and 300 kg N ha-1) experiments were conducted with two cultivars of corn in Henan province of China. Results indicated that N fertilization affected yield, plant biomass, plant N content, and leaf area index. The values of NNI and NDC were from 0.54 to 1.28 and from -28.13 to 21.99 kg ha-1 under the different treatments of N rate, respectively. The NDC and NNI showed significantly negative relationships from V6 to the V12 stages. The values of PNP and FIPAR increased gradually with crop growth process. The PNP values gradually declined while the FIPAR values of every leaf layer increased with the increase of N supply. The NDC-PNP, NNI-FIPAR relationships were significantly positive, however, the relationships between NNI-PNP and NDC-FIPAR were significantly negative during vegetative period of corn. The coefficient of determination (R2) based on NNI was better than that on NDC. The FIPAR values were near to 0.35, 0.67, and 0.76 % at the upper, middle, and bottom of leaf layer, and PNP values were approximately 39, 44, and 51 kg kg-1 at V6, V9, and V12 stages, when NNI and NDC values were equal to 1 and 0 kg ha-1, respectively. This study described the quantitative information about the effect of plant internal N deficit to plant N productivity and canopy light intercept. The projected results would assist in predicting the appropriate plant growth status during key N top-dressing stages of corn, which can optimize N application and improve N use efficiency.